2015
DOI: 10.1002/ar.23124
|View full text |Cite
|
Sign up to set email alerts
|

Apoptotic Mediators are Upregulated in the Skeletal Muscle of Chronic/Progressive Mouse Model of Parkinson's Disease

Abstract: Apoptosis has been implicated in the pathogenesis of Parkinson disease (PD). Parkinson disease is characterized by skeletal muscle abnormalities. The aim of this study is to illustrate the impact of PD induction on the expression of apoptotic mediators. Twenty normal albino mice were randomly selected and equally divided in control and PD groups. Chronic Parkinsonism was induced in the PD group using 1-methyl-4-phenyl-1,2,3,6-tetrahydropyridine and probenecid (MPTP/p). After that, samples from gastrocnemius mu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
19
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 78 publications
3
19
0
Order By: Relevance
“…This is consistent with previous studies that skeletal muscle fibers are capable of producing proinflammatory factors [118,127]. These proinflammatory cytokines are overexpressed in PD-induced skeletal muscle cells [116,128,129]. However, after physical training, overexpressed inflammatory cytokines are inhibited in aging skeletal muscle [64,122].…”
Section: Physical Exercise Can Reduce Inflammation Andsupporting
confidence: 93%
“…This is consistent with previous studies that skeletal muscle fibers are capable of producing proinflammatory factors [118,127]. These proinflammatory cytokines are overexpressed in PD-induced skeletal muscle cells [116,128,129]. However, after physical training, overexpressed inflammatory cytokines are inhibited in aging skeletal muscle [64,122].…”
Section: Physical Exercise Can Reduce Inflammation Andsupporting
confidence: 93%
“…through a variety of signaling pathways [10]. Many studies have demonstrated that abnormalities in p53 protein promote the development of PD by targeting the regulation of apoptosis-related genes [11,12]. Induction of apoptosis is an important mechanism by which p53 exerts tumor suppressor function in cancer [13,14].…”
Section: Discussionmentioning
confidence: 99%
“…Animal-related protocols were carried out according to the recommendations of the Institutional Animal Care and Use Committee at Jordan University of Science and Technology. A previously described protocol was used to induce chronic Parkinson disease in the mice [27,28]. In summary, intraperitoneal doses of 1-methyl-4-phenyl-1,2,3,6-tetrahydropyridine hydrochloride (25 mg/kg) and subcutaneous doses of probenecid (250 mg/kg) were administered in PD mice every 3.5 days for 5 weeks.…”
Section: Methodsmentioning
confidence: 99%
“…Then, serial longitudinal 4-μm–thick paraffin-embedded sections were cut. The sections were processed via immunohistochemistry according to previously described protocols [28,3036]. To summarize, the sections were firstly deparaffinized and rehydrated.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation